The commemoration of death, organizational memory, and police culture - Sierra-Arévalo, Michael (Criminology, 2019)
Police scholars document that although there is fragmentation of the so‐called “monolithic” police culture, historically consistent features of the occupational culture of police exist. By drawing on ethnographic observations in three U.S. police departments, I describe how one consistent feature of police culture—the preoccupation with danger and potential death—is maintained by the commemoration of officers killed in the line of duty. Through the use of commemorative cultural artifacts, officers and departments construct an organizational memory that locally reflects and reifies the salience of danger and potential death in policing. Furthermore, commemoration of fallen officers is not restricted to a department's own; the dead of other departments are commemorated by distant police organizations and their officers, maintaining broad, occupational assumptions of dangerous and deadly police work that transcend a single department and its localized organizational memory. Implications for the study of police culture, inequalities in policing, and police reform are considered.